Збереження та ретрансляція етнічної ідентичності дисперсно розселених субетнічних груп в іноетнічному середовищі (на прикладі цалкінських греків Харкова) - Гулая, О.C. (Культура народов Причерноморья, 2013)
Розглянуті умови та фактори збереження етнічної ідентичності представниками
субетнічної групи цалкінських греків Харкова, виявлено роль традиційної культури в процесі
ретрансляції ідентичності наступним поколінням. Проаналізовано специфіку динаміки етнічної
культури греків – цалкінців в умовах дисперсного розселення в урбанізованому середовищі. Визначено
чинники, що визначають зміни в етнічній самосвідомості урумської грецької міської спільноти Харкова. Рассмотрены условия и факторы сохранения этнической идентичности представителями
субэтнической группы цалкинских греков Харькова, выявлена роль традиционной культуры в процессе
ретрансляции идентичности последующим поколениям. Проанализирована специфика динамики
этнической культуры греков - цалкинцив в условиях дисперсного расселения в урбанизированной среде.
Обозначены факторы, определяющие изменения в этническом самосознании урумского греческой
городского сообщества Харькова. The conditions and factors of ethnic identity conservation of the Tsalkins Greeks sub-ethnic group in
Kharkiv are investigated. The role of traditional culture in the identity transfer to future generations is analyzed.
The conclusion about the threat of Greeks ethnic culture loss in a dispersed settlements in the urban
environment is made.
We found that Tsalkins Greeks remain very robust imagination of their own ethnicity and high level of ethnic
identity in spite of ignorance of the native language, impossibility to follow their tradition, the gradual loss of
cultural heritage.
During the late 1990s - early 2000s the process of the unique culture of Pontic Greeks destruction began. This
culture combines the features of archaic Greek, Byzantine and Anatolian cultures.
Tsalkins Greeks, who were forced to migrate, gradually lose their language and culture in dispersed settlement.
Since the advent in Georgia the Greek community focused on isolation and preservation of identity. When they
were forced to emigrate from Georgia and dispersed settled in dispersion in towns and villages of Greece,
Russia, Ukraine, their culture and traditions remained under threat of complete assimilation.
Greeks believe that alliance of the Greek community representatives (to celebrate the religious and family
holydays and feast-days (baptisms, weddings, anniversaries), play rituals and traditions by the "parent"
scenario, mono-ethnic marriages, retelling stories about history of Greeks people and their families to children
will help to preserve ethnic identity and transfer it to future generations.